Transport and transformation of surface water masses across the Mascarene Plateau during the Northeast Monsoon season. Issue 4 (2nd October 2017) - Vianello, P; Ansorge, IJ; Rouault, M; Ostrowski, M
Abstract : The Mascarene Plateau lies in the south-west Indian Ocean between the islands of Mauritius and the Seychelles Bank, and is characterised by a series of shallow banks separated by deep (>1 000 m), narrow channels. The plateau acts as an obstruction to the general ocean circulation in this region, separating the westward-flowing South Equatorial Current (SEC) into two branches downstream of the plateau. In this article, we present the results of a survey conducted along the entire Mascarene Plateau during the Northeast Monsoon, in October–November 2008. In addition, data from Argo floats were used to determine the origin of water masses entering this region. The plateau contains three gaps through which branches of the SEC are channelled. The northern, central and southern gaps receive 14.93 Sv, 14.41 Sv and 6.19 Sv, respectively. Although there are differences in water-mass properties to the west and east of the Mascarene Plateau due to mixing, the SEC acts as a sharp boundary between water masses of southern and northern Indian Ocean origin. Mixing occurs in the central gap between intermediate water masses (Red Sea Water [RSW] and Antarctic Intermediate Water [AAIW]) as well as in the upper waters (Subtropical Surface Water [STSW] and Indonesian Throughflow Water [ITW]). Through the northern gap, mixing occurs between Arabian Sea High-Salinity Water (ASHSW), ITW and Tropical Surface Water (TSW), while through the southern gap, mixing occurs between STSW and ITW. North Indian Deep Water (NIDW) is present in the region but the plateau appears to have no effect on it.